Infection-associated decline of Cape buffalo blood catalase augments serum srypanocidal activity - Wang, Q.; Murphy, N.; Black, Samuel J. (1999)
Clearance of trypanosomes from the blood of infected Cape buffalo was associated with the development of two responses: (i) complement-dependent and clone-specific lytic activity and (ii) complement-independent trypanocidal activity that was not restricted by trypanosome clone or species. This latter activity was mediated by H2O2 and required the presence of xanthine oxidase in serum but not the addition of purine substrates. Expression of the xanthine oxidase-dependent trypanocidal activity in Cape buffalo serum was coincident with, and required, a decline in its H2O2 catabolic activity. The H2O2 catabolic activity of Cape buffalo serum was due solely to catalase and declined by eightfold around the time that trypanosomes were cleared from the blood, accompanied by a fivefold drop in erythrocyte-associated catalase activity. The Cape buffalo did not develop subsequent parasitemic waves. Clearance of parasitemia in similarly infected cattle was also associated with development of trypanosome clone-specific lytic activity, but not with the acquisition of H2O2-dependent trypanocidal activity in serum, and the cattle supported recurring parasitemia. The lack of trypanocidal activity in pre- and postinfection cattle sera was due to their low content of xanthine oxidase and sustained catalase activity. These data strongly suggest that an infection-induced serum oxidative response, the efficacy of which is amplified by a decline in blood catalase, contributes to suppression of recurring parasitemia in Cape buffalo.